Transcirculation microballoon-assisted coil embolization for dorsal pancreatic artery aneurysm due to celiac artery dissection: A case report - Takara, Yuki (SAGE Open Med Case Rep, 2021)
The dorsal pancreatic artery is a part of peripancreatic arcade connecting celiac artery to transpancreatic artery. A dorsal pancreatic artery aneurysm derived from dissection of celiac artery is a rare pathology, and it sometimes requires ingenious strategy in an endovascular surgery. Hereby, we report a case of a patient who underwent coil embolization for dorsal pancreatic artery aneurysm due to celiac artery dissection by applying transcirculation approach of a balloon catheter through the peripancreatic arcade, which was successfully achieved.